One year after: Has the COVID-19 pandemic increased violence in sub-Saharan Africa? - Matthias Basedau; Mora Deitch (German Institute of Global and Area Studies (GIGA), 2021)
In spring 2020, observers and practitioners warned that COVID-19 would increase violence in sub-Saharan Africa by creating an economic shock that would lead to distributional conflicts and government repression. Compared to before the pandemic, violence did increase in 2020, rising by 40 and 60 per cent in terms of fatalities and events, respectively. Controlling for important confounders, COVID-19 proves significant to the increase in violence in many models; however, a robust effect can be found only for "COVID-19 unrest," which forms a fraction of the violence and stems from the stringency of government reactions rather than the pandemic itself. Pre-pandemic fragility accounts best for the region's rise in violence. Expert assessments confirm these findings but also yield evidence warning against prematurely announcing an all-clear. The fallout of the pandemic on conflict is likely to have a longer period of incubation, and there are initial indications that conditions will worsen.
Keywords: 300; COVID-19; armed conflict; fragility; sub-Saharan Africa; unrest; restrictions